Some Field Observations on Dendrocalamus hamiltonii - Dubey, R. M. (Indian Forester, 1991)
The field observations on Dendrocalamus hamiltonii suggest that repeated injury or damage to the culms of these bamboos cause branching / coppicing from the node of rhizome attached portion of the culms cut which is responsible for the congestion of these culms making them difficult for harvesting. It is suggested that congested clumps should almost be clearfulled at the time of working to remove total congestion. The coppicing potentiai of these bamboos should be exploited for making trials for their vegetative propagation through rooted culm cuttings. It is also suggested that at the time of cutting the culms should be cut at a height of above one feet above the ground leaving not more than one node to check coppicing.